Air and Space Law Education: Preparing for the Future in China, Indonesia, Italy and Thailand - Nugraha, Ridha Aditya; Kong, Dejian; Guiso, Gaia; Kovudhikulrungsri, Lalin (Faculty of Law, Hasanuddin University, 2021)
Aerospace technology has developed rapidly within the last decade. Facing the future, there is an urgency to balance aerospace technology developments with providing sufficient human resources through education, in this context from the perspective of air and space law. From east to west, this article elaborates on air and space law education in four countries with different experiences in aerospace activities, namely China, Thailand, Indonesia, and Italy. The development of higher education in conducting such programs is essential to ensure that the national aerospace industry will never lack proper human resources from its own nationals, including professionals with specific air and space law expertise. Furthermore, higher education has a significant role in bridging the industry with recent developments and advising the government in setting up aviation and space policies, as in the successful case of China and Italy. In the end, this article provides policy recommendations on promoting air and space law in higher education.